YIV-818-A: a novel therapeutic agent in prostate cancer management through androgen receptor downregulation, glucocorticoid receptor inhibition, epigenetic regulation, and enhancement of apalutamide, darolutamide, and enzalutamide efficacy - Lam, Wing; Arammash, Mohammad; Cai, Wei; Guan, Fulan; Jiang, Zaoli; Liu, Shwu-Huey; Cheng, Peikwen; Cheng, Yung-Chi (Frontiers in Pharmacology, 2023)
Introduction: Prostate cancer is the second leading cause of cancer death among men in the United States. Castration-Resistant Prostate Cancer (CRPC) often develops resistance to androgen deprivation therapy. Resistance in CRPC is often driven by AR variants and glucocorticoid receptor (GR). Thus, drugs that target both could be vital in overcoming resistance. Methods: Utilizing the STAR Drug Discovery Platform, three hundred medicinal plant extracts were examined across 25 signaling pathways to identify potential drug candidates. Effects of the botanical drug YIV-818-A, derived from optimized water extracts of Rubia cordifolia (R.C.), on Dihydrotestosterone (DHT) or Dexamethasone (DEX) induced luciferase activity were assessed in 22RV1 cells harboring the ARE luciferase reporter. Furthermore, the key active compounds in YIV-818-A were identified through activity guided purification. The inhibitory effects of YIV-818-A, RA-V, and RA-VII on AR and GR activities, their impact on AR target genes, and their roles in modifying epigenetic status were investigated. Finally, the synergistic effects of these compounds with established CRPC drugs were evaluated both in vitro and in vivo. Results: YIV-818-A was found to effectively inhibit DHT or DEX induced luciferase activity in 22RV1 cells. Deoxybouvardin (RA-V) was identified as the key active compound responsible for inhibiting AR and GR activities. Both YIV-818-A and RA-V, along with RA-VII, effectively downregulated AR and AR-V proteins through inhibiting protein synthesis, impacted the expression of AR target genes, and modified the epigenetic status by reducing levels of Bromodomain and Extra-Terminal proteins (Brd2/Brd4) and H3K27Ac. Furthermore, these compounds exhibited synergistic effects with apalutamide, darolutamide, or enzalutamide, and suppressed AR mediated luciferase activity of 22RV1 cells. Co-administration of YIV-818-A and enzalutamide led to a significant reduction of 22RV1 tumor growth in vivo. Different sources of R.C. had variable levels of RA-V, correlating with their potency in AR inhibition. Discussion: YIV-818-A, RA-V, and RA-VII show considerable promise in addressing drug resistance in CRPC by targeting both AR protein and GR function, along with modulation of vital epigenetic markers. Given the established safety profile of YIV-818-A, these findings suggest its potential as a chemopreventive agent and a robust anti-prostate cancer drug.